Anxiety in Patients with Chronic Cor Pulmonale and Its Effect on Exercise Capacity - Wenxin XU; Jiwei YAO; Longfei CHEN (Tehran University of Medical Sciences, 2016)
Background: Chronic cor pulmonale (CCP) is a disease of increasing frequency in Chinese people and profoundly influences their health. CCP is often accompanied by anxiety and other psychological problems, and patients may show signs of motor function decline. However, little attention has been paid to the impact of CCP-related psychological problems on motor function. Methods: Patients with CCP receiving in- or outpatient treatment in the Respiratory Department of Xiangya Hospital of Central South University and the Second Xiangya Hospital of Central South University in Hunan Province between January and July 2015 were investigated. A total of 167 questionnaires were distributed, with 160 valid questionnaires ultimately collected from 95 male and 65 female participants of mean age (± standard deviation) of 68.2 ± 12.3 yr. Self-Rating Anxiety Scale (SAS) scoring was adopted to evaluate anxiety in the participants, and heart rate, blood pressure, breathing rate, 6-minute walk test and Borg index score were combined to detect the exercise capability of the participants. Results: Anxiety was present in 48.8% of patients. Heart rate, systolic blood pressure, breathing rate and the Borg score of CCP patients with anxiety were higher than in CCP patients without anxiety (P < 0.05), while mean walking distance was shorter (P < 0.05). Conclusion: The rate of anxiety in patients with CCP is relatively high. Anxiety reduces motor function in CCP patients; therefore, in the process of treating patients with CCP, effort should be made to engage simultaneously patients in psychotherapy.